The Effectiveness of Digital Storytelling in Enhancing Language Skills among Children Aged 5-6 Years - Laila Nursafitri (Pt. Anagata Sembagi Education, 2026)
Language competence between ages five and six predicts later literacy, academic achievement, and social participation, yet many kindergarten classrooms still rely on static, teacher-centred storytelling that struggles to sustain young children's attention. Digital storytelling (DST), combining narrative text with animation, sound, images, and interactivity, has emerged as a promising alternative, but evidence remains scattered across small-scale classroom action research, quasi-experiments, and descriptive studies conducted mainly in Indonesian early childhood settings. This article synthesises twenty-five peer-reviewed, DOI-verified studies published mainly between 2021 and 2025 to evaluate the effectiveness of digital storytelling in enhancing receptive, expressive, and narrative language skills among children aged 5-6 years. Using a structured narrative literature review method, articles were identified, screened, and analysed against explicit inclusion criteria. The synthesis shows digital storytelling consistently produces meaningful gains in vocabulary, sentence construction, listening comprehension, and speaking confidence compared with conventional methods, with effect sizes moderated by media type, session frequency, and teacher facilitation. The novelty of this review lies in its comparative mapping of media modalities-animation, website-based platforms, augmented reality, and bilingual applications-against specific language sub-skills, an integration largely absent from prior single-study reports. Implications for early childhood curriculum design and future research are discussed.